Implications of a new licensing framework on the impact assessment of water and sewage systems (Sustainability in Debate, 2022)
A bill pending in the Brazilian Senate may change profoundly the characteristics and practice of environmental licensing in Brazil, including removing the obligation to obtain an environmental license for specific projects, such as those related to water supply and sanitary sewage. This timely bibliographical and documental study aims to analyse the development of specific legislation on environmental impact assessment (EIA) and environmental licensing of these two types of projects and compare them with the changes provided by the proposed Licensing Law. The work uses the identification and analysis of specific rules and legal documents that make up the current regulatory framework for licensing and the changes provided by the bill. The flexibility and exclusion of environmental licensing, without scientific rigour, ignore the importance of this instrument for environmental integration into decision-making. Furthermore, projects could damage the environment without such analysis due to the need to expand water supply and sanitation systems.